Proceedings of the 2004 IEEE International Conference on Solid Dielectrics, 2004. ICSD 2004. 2004
DOI: 10.1109/icsd.2004.1350315
|View full text |Cite
|
Sign up to set email alerts
|

The effect of degassing on morphology and space charge

Abstract: It is believed that space charge buildup in cross-linked polyethylene (XLPE) insulation is one of the main cause for premature failure of underground power cables. The space charge activities in XLPE depend on many factors such as additives, material treatment, ambient temperature, insulator/electrode interface, etc. Degassing is one of the material treatment processes commonly employed in cable manufacturing to improve insulation performance. In this paper, investigation on the effect of degassing period on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…The network not only improves the heat resistance, but also can enhance durability such as more resistance towards chemical and stress cracking [3]. Thermal and mechanical properties of PE can be significantly enhanced by the crosslinking process [4] and for this reason, XLPE cables are the best choice in power industry for high voltage applications. In crosslinking, the polymer chains are linked together through chemical reaction by the activation of crosslinking agent under high temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The network not only improves the heat resistance, but also can enhance durability such as more resistance towards chemical and stress cracking [3]. Thermal and mechanical properties of PE can be significantly enhanced by the crosslinking process [4] and for this reason, XLPE cables are the best choice in power industry for high voltage applications. In crosslinking, the polymer chains are linked together through chemical reaction by the activation of crosslinking agent under high temperature.…”
Section: Introductionmentioning
confidence: 99%
“…91 A number of experiments have been designed for the clarification how the crosslinking byproducts affect the space charge formation and which byproduct is the dominant. 69,88,[92][93][94] For instance, Maeno et al 69,[92][93][94] reported that cumyl-alcohol is responsible for homo-charge in LDPE and XLPE, acetophenone for heterocharge in XLPE, and -methylstyrene has no effect in LDPE but provides traps in XLPE. It is believed that space charge can be significantly reduced with a proper elimination of all the crosslinking by-products (de-gassing), water, and carbonyl groups.…”
Section: Additives and Cross-linking By-productsmentioning
confidence: 99%
“…If the level of the byproducts changes significantly over time, the dielectric properties of the insulation in the cable can change. The electrical performance of the cable can be altered if such a change occurs after it is installed [5]. Of particular concern is the volatilization of these materials.…”
mentioning
confidence: 99%